Post-Omicron SARS-CoV-2 antibody prevalence in Sierra Leone: A cross-sectional, nationally representative, follow-up serosurvey. - Smit Chitre; Mohamed Bailor Barrie; Joseph Sam Kanu; Theophilus S Conteh; Mohamed Bayoh; Matilda N Kamara; Haja Fatmata Bangura; Jonathan S Lascher; Raphael Frankfurter; Sarah A Goldberg; David V Glidden; J Daniel Kelly; et al. (PLOS Global Public Health)
Based on a serosurvey conducted in March 2021, Barrie and colleagues published the first nationally representative SARS-CoV-2 serosurvey in Africa, estimating a SARS-CoV-2 seroprevalence of 2.6% in Sierra Leone, 43 times higher than the reported number of cases at that time. Over the following two years, increasingly transmissible variants-specifically Delta and Omicron-proliferated across the globe, and their impact in Africa is poorly understood. Additional nationally representative seroprevalence data are therefore necessary to understand the pandemic's progression on the continent and for evaluating containment measures and future preparedness. Our follow-up nationally representative survey was conducted in Sierra Leone from February to March 2023. We returned to the 120 Enumeration Areas throughout the country collecting blood samples from one or more individuals per household as well as information on sociodemographic characteristics, history of COVID-19 infection and immunization, and attitudes towards vaccination. The weighted overall seroprevalence (vaccinated and/or SARS-CoV-2 infection) for individuals >19 years of age was 33% (95% CI 29-37). Using the data and distributions from our previous serosurvey, the weighted predicted seroprevalence (any prior SARS-CoV-2 infection) for the general population was 28% (95% CI 15-41). The weighted predicted seroprevalence was ~11 times higher than the pre-Delta/Omicron prevalence. It was also over 300 times higher than the reported number of cases. Despite this, overall seroprevalence was low compared with countries in Europe and the Americas (pointing towards lower transmission in Sierra Leone). In addition, our results suggest the following regarding prevention campaigns claiming to have vaccinated 70% of adults in Sierra Leone as of December 2022: 1) they resulted in limited seroconversion; 2) there was significant waning of immunity; and/or 3) many less individuals were vaccinated than reported. Regardless of the cause, the utility of COVID-19 Vaccine Delivery Partnership (CoVDP) efforts three years into the pandemic is called into question.